The Utilization of Diagnostic Musculoskeletal Ultrasound in the Evaluation for Ischiofemoral Impingement: A Perspective for Rehabilitation Providers - Robert C. Manske; Chris Wolfe; Phil Page; Michael Voight; Beth Bardowski (International Journal of Sports Physical Therapy)
Ischiofemoral impingement (IFI) is a significant but often underdiagnosed source of deep posterior hip pain and functional impairment, frequently associated with narrowing of the ischiofemoral space (IFS) between the ischial tuberosity and the lesser trochanter of the femur. Traditionally, diagnostic approaches for IFI have relied on clinical examination and magnetic resonance imaging (MRI). However, the advent of diagnostic musculoskeletal ultrasound (MSKUS) has transformed the evaluation process. MSKUS offers a non-invasive, cost-effective, and dynamic method for assessing the IFS and associated musculature in real time, allowing for high-resolution visualization of soft tissues, bones, and neurovascular structures. For rehabilitation providers, understanding the application, strengths, and limitations of MSKUS can enhance diagnostic accuracy, guide targeted therapeutic interventions, and potentially expedite recovery. This article reviews the anatomy of the IFS, the pathophysiology of IFI, and the use of MSKUS in diagnosing IFI, equipping rehabilitation professionals with the knowledge to integrate this valuable diagnostic tool into clinical practice.